Three new species of the genus Lepidostoma Rambur (Lepidostomatidae: Trichoptera) from India - Parey, Sajad H.; Morse, John C.; Pandher, Manpreet S. (Zootaxa, 2016)
Three new species of the genus Lepidostoma Rambur are described and illustrated from the Indian Himalaya: Lepidostoma trilobatum sp. nov., L. lidderwatense sp. nov., and L. sainii sp. nov., all belonging to the Lepidostoma ferox Branch. With these new additions, the genus Lepidostoma is now represented by 50 species in India and over 450 species globally.